Analisis Spasial Bentuk Lahan dan Potensi Kebencanaan pada Koridor Jalan Lingkar Regional - Andi Sulia Sudirman; Sitti Kasmiati; Nur Hasanah (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
The construction of the Gorontalo Outer Ring Road (GORR) in hilly terrain carries a high potential for disaster risk. Therefore, a study of the physical land characteristics is crucial to support disaster risk mitigation along the route. This study aims to analyze the landform and disaster potential in the GORR area. The research was conducted through spatial analysis supported by field surveys and historical landslide information from local communities. Geomorphological, analysis indicates that the GORR area lies within denudational hills. Based on the Regional Geological Map of the Tilamuta Sheet, the exposed lithology is dominated by clastic limestone units (TQl), Bilungala volcanic rocks (Tmv), Bone diorite (Tmb), and lake deposits (Qpl). Land cover includes the GORR road, gardens, fields, and shrubs, with maize and coconut plantations that can accelerate surface erosion due to their limited capacity to retain water.Steep slopes further increase the risk of landslides, which pose a danger to road users and nearby communities. Therefore, disaster mitigation strategies are needed, including the delineation of landslide-prone zones and the installation of warning signs at critical points to enhance public awareness, especially during the rainy season. These efforts support sustainable development and disaster risk reduction in the GORR region.